2017
DOI: 10.1016/j.jcmg.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Predictors, and Clinical Presentation of a Calcified Nodule as Assessed by Optical Coherence Tomography

Abstract: The presence of a CN was associated with severe calcification and larger hinge movement of the coronary artery (especially ostial and mid right coronary artery). One-third of the underlying plaque morphology of severely calcified culprit lesions in patients with ACS was caused by a CN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
118
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 137 publications
(134 citation statements)
references
References 32 publications
14
118
2
Order By: Relevance
“…A CN is a cause of stable angina or acute coronary syndrome. Lee et al reported that CNs have a tendency to exist in the ostial or middle RCA with tortuosity, and that one-third of acute coronary syndrome lesions with severe calcified plaque had a CN [2]. In addition, it has been shown that a CN increases the risk of stent failure both in the early and late phases [3].…”
Section: Discussionmentioning
confidence: 99%
“…A CN is a cause of stable angina or acute coronary syndrome. Lee et al reported that CNs have a tendency to exist in the ostial or middle RCA with tortuosity, and that one-third of acute coronary syndrome lesions with severe calcified plaque had a CN [2]. In addition, it has been shown that a CN increases the risk of stent failure both in the early and late phases [3].…”
Section: Discussionmentioning
confidence: 99%
“…This HRP feature is associated with unstable plaque morphology, culprit lesions in acute coronary syndromes, and accelerated plaque progression despite the use of medical therapy. [28][29][30][31] The combination of a greater plaque volume and higher prevalence of spotty calcification in patients with LM disease suggest a more aggressive atherosclerosis process which may be driving LM disease rather than a result of it. In support of this is that the greater rate of plaque progression was present independent of coronary artery site, with equally advanced rates of plaque progression occurring in the right coronary artery as in the proximal LAD and LCx suggesting a systemic rather than localized process.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the larger number of patients with T2D than without (63.6% vs. 10.9%) using statins, which may reduce TCFAs and plaque rupture (26). The universally acknowledged features of vulnerable plaques currently include TCFAs, macrophage accumulation, calcified nodules, vasa vasorum and cholesterol crystals (27)(28)(29)(30)(31). The association between TCFAs and CVRFs was described above.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%